1962
DOI: 10.1902/jop.1962.33.4.328
|View full text |Cite
|
Sign up to set email alerts
|

Mucogingival Surgery: The Apically Repositioned Flap

Abstract: T HERE is no aspect of periodontal surgery that is in as great a state of confusion and flux as is that of mucogingival surgery. Since its inception a multiplicity of operations have been devised, modified and remodified; all with an eye to achieving maximum results with a minimum amount of trauma to the patient. The objectives of mucogingival surgery have been delineated clearly but the means of realizing these objectives have not been systematically devised. At this writing there remains the task of selectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 6 publications
1
70
0
10
Order By: Relevance
“…A certain amount of keratinized tissue has been considered necessary for maintaining periodontal health [3,4] .It was also concluded that for the maintenance of gingival health 2mm of keratinized gingiva is adequate [5] .Since an adequate amount of keratinized tissue is yet to be decided, the resolution to increase the width of keratinized gingiva still depends upon the preference of clinician. Historically, the methods to augment keratinized tissue included-1) an apically positioned flap (APF), 2) an APF in conjunction with autogenous tissue and, 3) an APF in conjunction with allogenic tissue [6][7][8] . Autogenous soft tissue grafting procedures have also been proposed to surgically correct localized alveolar deficiencies, as a preparation and development of the site during pre-prosthetic surgeries, and as ridge preservation procedures [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…A certain amount of keratinized tissue has been considered necessary for maintaining periodontal health [3,4] .It was also concluded that for the maintenance of gingival health 2mm of keratinized gingiva is adequate [5] .Since an adequate amount of keratinized tissue is yet to be decided, the resolution to increase the width of keratinized gingiva still depends upon the preference of clinician. Historically, the methods to augment keratinized tissue included-1) an apically positioned flap (APF), 2) an APF in conjunction with autogenous tissue and, 3) an APF in conjunction with allogenic tissue [6][7][8] . Autogenous soft tissue grafting procedures have also been proposed to surgically correct localized alveolar deficiencies, as a preparation and development of the site during pre-prosthetic surgeries, and as ridge preservation procedures [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…13.12). The apically positioned flap (Friedman 1962) is a mucoperiosteal internal bevelled flap, positioned at the (1)…”
Section: Surgical Elimination or Reduction Of Deep Pocketsmentioning
confidence: 99%
“…Long term studies of advanced furcation involvement have demonstrated poor survival rates. [1] Many treatment modalities are available to treat the furcation like scaling and root planing (non-surgical approach), [1] osteoplasty/ostectomy, odontoplasty, [2] surgery to increase the access to furcation area, [3] root resection/root amputation, [4] bicuspidization (to remove furcation), tunnel procedure, [5] guided tissue regeneration and a combination of graft materials and membranes. [6] Glickman [1] classified furcation invasion into four classes.…”
Section: Introductionmentioning
confidence: 99%